1996
DOI: 10.1177/0272989x9601600209
|View full text |Cite
|
Sign up to set email alerts
|

Angina Patients' Ratings of Current Health and Health without Angina

Abstract: Severity of comorbidity was a better predictor of patients' current health rating, rating for angina-free health, and anticipated gain from relief of angina than was severity of angina. Since patient perceptions of a symptom may be distinct from self-reported symptom severity, treatment-outcome studies should assess patient preferences in addition to symptom severity. Comorbidity should also be measured in such studies. Having patients rate current health and symptom-free health may be a useful measure of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Therefore, the Vitality scale appears to be less valid for measuring physical health in Taiwan than in the West. Such a relationship between Vitality and the Mental Health dimension has also been seen in other studies of Chinese-Americans[8,24] Subjects in the abovementioned samples are all familiar with the culture of traditional Chinese medicine; hence the results may reflect how people perceive their vitality status within a cultural framework. In the traditional theory of Chinese medicine, the phrase ("JingShen") associated with the presence of vitality is used to describe "mental well-being" [25].…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, the Vitality scale appears to be less valid for measuring physical health in Taiwan than in the West. Such a relationship between Vitality and the Mental Health dimension has also been seen in other studies of Chinese-Americans[8,24] Subjects in the abovementioned samples are all familiar with the culture of traditional Chinese medicine; hence the results may reflect how people perceive their vitality status within a cultural framework. In the traditional theory of Chinese medicine, the phrase ("JingShen") associated with the presence of vitality is used to describe "mental well-being" [25].…”
Section: Discussionsupporting
confidence: 73%
“…It was validated against measures such as physician diagnoses, nitroglycerin refills, and exercise duration and has subsequently been shown to be prognostic of outcome . The SAQ can distinguish treatment effect from the influences of comorbid illness and is more sensitive to subtle changes in clinical condition than are generic measurement tools .…”
Section: Methods Of Assessing Qolmentioning
confidence: 99%
“…The Mental Health and Energy domains were unable to differentiate between people with CHD who received a health promotion intervention and those who received usual services [15]. In patients with angina, studies [12,16,24] revealed that the SF-36 domains were unable to distinguish between clinical classes of angina (determined by the Canadian Cardiac Society's (CCS) classification system) and all domains have a low correlation with patients' single item ratings of current health [17]. However, all of the SF-36 domains, except Role Emotional, were found to differentiate significantly between CHD patients who were experiencing angina and those who had a history of angina but were not currently experiencing this symptom [12].…”
Section: Validitymentioning
confidence: 99%